Comparison of the Biochemical Properties and Roles in the Xyloglucan-Rich Biomass Degradation of a GH74 Xyloglucanase and Its CBM-Deleted Variant from Thielavia terrestris - Beibei Wang (International Journal of Molecular Sciences, 2022)
Xyloglucan is closely associated with cellulose and still retained with some modification in pretreated lignocellulose; however, its influence on lignocellulose biodegradation is less understood. TtGH74 from Thielavia terrestris displayed much higher catalytic activity than previously characterized fungal GH74 xyloglucanases. The carbohydrate-binding module 1 (CBM1) deleted variant (TtGH74ΔCBM) had the same optimum temperature and pH but an elevated thermostability. TtGH74 displayed a high binding affinity on xyloglucan and cellulose, while TtGH74ΔCBM completely lost the adsorption capability on cellulose. Their hydrolysis action alone or in combination with other glycoside hydrolases on the free xyloglucan, xyloglucan-coated phosphoric acid-swollen cellulose or pretreated corn bran and apple pomace was compared. CBM1 might not be essential for the hydrolysis of free xyloglucan but still effective for the associated xyloglucan to an extent. TtGH74 alone or synergistically acting with the CBH1/EG1 mixture was more effective in the hydrolysis of xyloglucan in corn bran, while TtGH74ΔCBM showed relatively higher catalytic activity on apple pomace, indicating that the role and significance of CBM1 are substrate-specific. The degrees of synergy for TtGH74 or TtGH74ΔCBM with the CBH1/EG1 mixture reached 1.22–2.02. The addition of GH10 xylanase in TtGH74 or the TtGH74ΔCBM/CBH1/EG1 mixture further improved the overall hydrolysis efficiency, and the degrees of synergy were up to 1.50–2.16.